Trying to Make a Good First Impression: A Natural Field Experiment to Engage New Entrants to the Tax System - Sarah Dong; Mathias Sinning (Institute of Labor Economics (IZA), 2021)
Very little is known about the compliance behavior of first-time taxpayers although their tax paying habits may affect the long-run functioning of a tax system. This paper studies the compliance behavior of new entrants to the tax system using data from a large-scale natural field experiment that was implemented in collaboration with the Australian Taxation Office (ATO). We examine the effectiveness of a welcome letter from the tax authority that aims to nudge first-time taxpayers to lodge their first income tax return. We compare this letter to a standard letter that emphasizes the possibility of penalties and interest charges. We find that both letters have surprisingly similar effects on tax compliance, suggesting that the main channel through which the letters affect individual behavior is by providing information. By contrast, the type of messaging and the way in which information is presented to first-time taxpayers appear to be relatively unimportant. Our analysis of heterogeneous treatment effects indicates that both letters are most effective for young entrants to the tax system and, within this group, more effective for Australian citizens than for visa holders.
Keywords: C93; H25; H26; 330; tax compliance; natural field experiment; behavioral insights